Effect of Bicarbonate-Rich Irrigation Waters on The Yield and Nutrient Uptake in Cotton (Gossypium spp) and Linseed (Linum Usitatissimum) - Paliwal, K V; Maliwal, G L; Nanawati, G C (Annals of Arid Zone, 2016)
Effect of increasing levels (4-12 meq/l) of bicarbonate ion concentration and residual sodium carbonate (1.25-5 meq/l) was studied in the greenhouse using quartz sand, on the growth and mineral nutrition of cotton (Gossypiium. spp.) and linseed (Linum usitatissimum). In irrigation waters of 40 meq/l, growth of these crops was decreased with increase of HC9T ion concentration. Cotton and linseed could grow well upto a bicarbonate ion concentration of 8 and 4 meqll respectively. At any RSC level, the adverse effect on the growth of these crops was in proportion to the CO3/ HCO3 ratio in irrigation water. The uptake of P, Ca and Mg was decreased and that of Na increased in both the crops but that of N and K was decreased in cotton and increased in linseed with the increase of HCO3 ion concentration and more so in presence of w. The specific effect of carbonate and/ or bicarbonate seems to inhibit the metabilic processes in the plant which may be responsible for the reduction of crop growth and abstetsorption of nutrients.